Agressividade e depressão em escolares - Silva, Diego Dewes da (2013)
This dissertation follows the rules proposed by the Graduate Program in Psychology at PUCRS and is divided in two studies. The first study is a systematic review of the literature, untitled Aggressiveness and Depression Expressions in Children and Adolescents: Systematic Review, whose objectives are: a) perform a systematic review of the literature about aggressiveness in children and adolescents assessed by the Children Behavior Checklist (CBCL); b) perform a systematic review of the literature about depression in children and adolescents assessed by the CBCL; c) to assess how aggression and depression manifest themselves in childhood and adolescence. Were used descriptors and criteria for inclusion and exclusion in pre-defined searches in the databases MedLine, Embase, PsycInfo, Lilacs, SCielo and BVS for the two systematic reviews performed considering specific descriptors for aggressiveness and depression, used in separate searches. It was found that children and adolescents manifest aggressiveness and depression in different ways according to sex and age around the world. The second study, untitled Age and Gender Differences in Aggressiveness and Depression in Schoolchildren aimed to analyze relationships existents between aggressiveness, anxiety-depression, withdrawn-depression, sex and age and to characterize the sample, which consists of schoolchildren protocols CBCL answered by parents. The results identified boys with significantly higher T scores than girls on the three subscales studied in CBCL. Was identified moderate positive association between aggressiveness, anxiety-depression and withdrawn-depression. Lastly, the manifestation of aggressiveness could be covering the depression more than half of the time.